1986
DOI: 10.1177/027347538600800205
|View full text |Cite
|
Sign up to set email alerts
|

Student Evaluations of Faculty: A Longitudinal Study from One Department in a Business School

Abstract: Student evaluations of professors' teaching effectiveness are in common use in universities. In many instances these evaluations are employed to evaluate faculty members for tenure and promotion decisions. The study showed that for one department in one university, student ratings of professors over a period of five years did not effectively distinguish among professors in the department.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

0
5
0

Year Published

1990
1990
2009
2009

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 6 publications
(5 citation statements)
references
References 3 publications
0
5
0
Order By: Relevance
“…A review of research in the Journal of Marketing Education and Marketing Education Review reveals 11 empirical articles during the past 20 years that investigated the topic. Cumulatively, this literature addresses issues such as halo effects (Orsini 1988), class size effects (Dommeyer 1997;Guseman 1985), generalizability (Wheeler and Geurts 1986), stability of instruction (Bharadwaj, Futrell, and Kantak 1993), and teaching experience (Clayson 1999).…”
Section: Studentevaluationofinstructorcreatesadebatethatstimu-mentioning
confidence: 99%
“…A review of research in the Journal of Marketing Education and Marketing Education Review reveals 11 empirical articles during the past 20 years that investigated the topic. Cumulatively, this literature addresses issues such as halo effects (Orsini 1988), class size effects (Dommeyer 1997;Guseman 1985), generalizability (Wheeler and Geurts 1986), stability of instruction (Bharadwaj, Futrell, and Kantak 1993), and teaching experience (Clayson 1999).…”
Section: Studentevaluationofinstructorcreatesadebatethatstimu-mentioning
confidence: 99%
“…The overall rationale for this model is that some perceptions of teaching develop before others and influence the final summative evaluation. For example, the literature suggests that students lack the confidence to evaluate their learning or are unable to make that determination (Clayson and Haley King 1983;Rodewald and Carroll 1974;Shamanske 1988;Wheeler and Guerts 1986). In their meta-analysis, Dowell and Neal (1982) suggest the following:…”
Section: Theoretical Modelmentioning
confidence: 99%
“…According to Larkin et al, "A sizable body of knowledge is prerequisite to expert skill, that knowledge must be indexed to large numbers of patterns that, on recognition, guide the expert in a fraction of a second to relevant parts of the knowledge store" (p. 1336). It is not surprising, then, that the literature seems to indicate that students either lack confidence or are relatively unable to make a determination of what they learned (King 1983;Rodewald and Carroll 1974;Shamanske 1988;Wheeler and Guerts 1986). A recent study by Harvard psychologists (Ambady and Rosenthal 1993) indicated that student reactions (i.e., nonenrolled student judges) to randomly selected 30-second clips of soundless videotapes of actual class instruction were extremely accurate predictors of end-of-course evaluations, even though the sound had been turned off.…”
Section: Figure 2: Theoretical Modelmentioning
confidence: 99%
“…Only a minority of studies that investigate student evaluations focuses on methodological and measurement aspects, and within these, the following problems have been identified: Student evaluations do not differentiate well between faculties (Wheeler and Geurts, 1986). They only distinguish between the very best and the very worst teachers (Wheeler and Geurts, 1986), and they capture "halo effects", which decrease as the overall rating of the instructor increases (Orsini, 1988).…”
Section: Prior Research -Student Evaluationsmentioning
confidence: 99%
“…They only distinguish between the very best and the very worst teachers (Wheeler and Geurts, 1986), and they capture "halo effects", which decrease as the overall rating of the instructor increases (Orsini, 1988). The validity of student evaluations is reduced by several language difficulties: (1) people do not have the necessary level of awareness to evaluate all aspects of a situation, (2) disagreement may exist regarding the object of the evaluation, (3) denotative and connotative meanings cannot be separated, (4) signs and meanings may be inconsistent and (5) the situation may affect the evaluation (Bertsch and Peek, 1982).…”
Section: Prior Research -Student Evaluationsmentioning
confidence: 99%